Feasibility and implementation of a healthy lifestyles program in a community setting in Ontario, Canada: protocol for a pragmatic mixed methods pilot study. Issue 10 (16th October 2019) - Alvarez, Elizabeth; Qutob, Majdi; Mbuagbaw, Lawrence; Lavis, John; Lokker, Cynthia; Walli-Attaei, Marjan; Samaan, Zainab; Sutton, Arielle; Singh, Japteg; Feeny, David; Fortuna, John
Abstract : Introduction: Rates of chronic conditions, such as diabetes, cardiovascular disease and obesity are increasing in Canada and internationally. There are effective lifestyle interventions that are known to improve chronic conditions. However, there is often a gap in 'how to' make lifestyle changes. Mental health and other determinants of health play a role in the development and progression of chronic conditions. Changing habits takes time and requires the use of multiple techniques, including mental health and behavioural change strategies, based on a person's needs. A new, multidisciplinary, person-centred and evidence-based and practice-based programme has been created to address these needs. This proposal aims to evaluate the feasibility and implementation of this programme and to determine changes in participant-directed and clinical outcomes through a pilot study. Methods and analysis: A pragmatic mixed methods design will be used to study multiple dimensions of the year-long healthy lifestyles programme. The pilot study includes a randomised controlled trial, with 30 participants randomised to either the programme or to a comparator arm, and qualitative components to determine the feasibility of the programme, including recruitment and retention, data missing rates and resources needed to run this programme. Changes in participant-directed and clinical outcomes will be measured. Descriptive statistics, t-tests and repeated measures analysis of variance (ANOVA) for within group comparisons and generalised estimating equations for between group analyses will be used. Qualitative interviews of programme staff and healthcare providers and family focus groups will be used to further enhance the findings and improve the programme. Ethics and dissemination: Approval from the Hamilton Integrated Research Ethics Board (HiREB) has been obtained. Informed consent will be obtained prior to enrolling any participant into the study. Participant IDs will be used during data collection and entry. Peer-reviewed publications and presentations will target researchers, health professionals and stakeholders. Trial registration number: ClinicalTrials.gov Identifier: NCT03258138 . HiREB project number: 3793.